METHODS OF DESIGN RESEARCH IN BRAND DESIGN TECHNOLOGY - TSIDYLO, Iryna; TSIDYLO, Khrystyna (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2024)
Abstract. This article discusses the application of design research methods in brand design technology. In the practice of graphic design, brand design technology follows a clearly defined algorithm. Design research methods serve as a key tool in the brand design algorithm, particularly during the research and hypothesis generation stages. The results of design research form the basis for formulating the brand metaphor. The ideas generated and the specific operationalized elements of the examined technology determine the thematic content of the "Corporate Identity" module in the educational component "Design Project" of the educational-professional program "Graphic Design."